2022
DOI: 10.1109/tap.2022.3184526
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Scattering Performance of Reflectarray Element Covered by Dielectric Superstrate

Abstract: In this paper, effect of a dielectric superstrate on scattering performance of reflectarray elements is clarified. At first, analytical electric field expressions of an infinite line current backed by a ground plane with the dielectric superstrate and so-called resonance conditions derived by Sugio et al., are reviewed. According to the electric field expressions and reciprocity, enhancement of the scattering field strength by the dielectric superstrate under the resonance conditions is expressed analytically.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Numerical simulation is performed and it is demonstrated that the predictions work for practical scatterers. This paper is enhancement of our previous work [4].…”
mentioning
confidence: 65%
“…Numerical simulation is performed and it is demonstrated that the predictions work for practical scatterers. This paper is enhancement of our previous work [4].…”
mentioning
confidence: 65%